Editorial An upcoming 30th anniversary encouraging the papers' publication - Salcedo, Nestor U. (2021)
We are proud to present the December edition, 52nd issue, of the Journal of Economics, Finance and Administrative Science (JEFAS), offering high-quality publications in English twice a year with double-blind peer-reviews. This standard provides us to be one of the most relevant empirical research open journals in the category of economics, econometrics and finance, according to SCImago Journal Rank, from Latin America to the World. Starting next year, this journal receives the 30th anniversary of its foundation as Cuadernos de Difusión. Therefore, this Editorial wants to start the celebrations by announcing the release of our new Open Journal System with the complete archive containing published papers since Vol. 1 No. 1 (March 1992). DOI: https://doi.org/10.1108/JEFAS-11-2021-329